Coupled effect of alkali concentration and metakaolin content on accelerated ageing of slag. Issue 3 (3rd May 2016) - Abdel Gawwad, H. A.; Khater, H. M.; Abd El-Aleem, S.
Abstract: This work aims at studying the effect of alkali concentration and metakaolin content on the resistivity of ground granulated blast-furnace slag (GGBFS) to strength regression during ageing. GGBFS was activated by 6 and 10 wt.% containing sodium hydroxide and liquid sodium silicate at a ratio of 1:1, respectively (namely GGBFS6 and GGBFS10 ). GGBFS10 was replaced by 10, 20, 30, 40 and 50 wt.% metakaolin, respectively. All hardened specimens were cured in 100% relative humidity (RH) at 37 ± 2 °C for 28 days (zero time), then aged at 95 °C for 56 days. The results showed that the pH value of GGBFS10 decreased as the amount of metakaolin increased. Also, the pH of GGBFS10 was higher than that of GGBFS6 . The strength regression resistivity (SRR) during accelerated ageing enhanced with the decrease in alkali concentration. The compressive strength for GGBFS6, GGBFS10 and GGBFS10 /metakaolin was evaluated. Some of the selected samples were analysed using infrared spectroscopy (FTIR), thermogravimetric analysis (TG/DTG) and X-ray diffraction (XRD) techniques to determine the mineralogical phase transition. The results are in a good harmony with those of FTIR, TG/DTG and XRD techniques and confirm that the SRR increases with metakaolin content.